2009
DOI: 10.1021/ci800419j
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM Calculations in Drug Discovery: A Useful Method for Studying Binding Phenomena?

Abstract: Herein we investigate whether QM/MM could prove useful as a tool to study the often subtle binding phenomena found within pharmaceutical drug discovery programs. The goal of this investigation is to determine whether it is possible to employ high level QM/MM calculations to answer specific questions around a binding event in a cycle time that is aligned with medicinal chemistry synthesis. To this end QM/MM calculations have been performed on four protein kinase-ligand complexes using five different levels of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 60 publications
0
50
0
Order By: Relevance
“…As a motivation of this work the authors claimed 23 that an involvement of the second water molecule in the catalytic mechanism was prompted by the cryotechnique studies by Scheidig, Burmester and Goody et al 38 This is an improper reference since in the latter work the GTP hydrolysis in Ras, but not in Ras-GAP has been experimentally studied. 39 The conclusions from the computations 23 suggesting that two water molecules operate in the cavity of the Ras·GTP·GAP complex are doubtful because of application of the semiempirical PM3…”
Section: New Piecesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a motivation of this work the authors claimed 23 that an involvement of the second water molecule in the catalytic mechanism was prompted by the cryotechnique studies by Scheidig, Burmester and Goody et al 38 This is an improper reference since in the latter work the GTP hydrolysis in Ras, but not in Ras-GAP has been experimentally studied. 39 The conclusions from the computations 23 suggesting that two water molecules operate in the cavity of the Ras·GTP·GAP complex are doubtful because of application of the semiempirical PM3…”
Section: New Piecesmentioning
confidence: 99%
“…Shortcomings of the PM3 methodology in describing hydrogen bonds, which is crucial for modeling protein systems, are well-known, e.g. ; 39 by these reasons more advanced procedures above PM3 have been introduced recent years. 40,41 Most likely, the protein structures obtained in Ref.…”
Section: New Piecesmentioning
confidence: 99%
“…This was an exhaustive procedure that took several days to finish. QM/MM has been shown to be a powerful tool for improving protein crystal structures [39], and it has proven reliable for studying protein-ligand binding phenomena [40].…”
Section: Qm/mm-pb/sa Can Accurately Reproduce the Biological Activitimentioning
confidence: 99%
“…QM/MM can be used for preparing the structures of small molecules and proteins, such as optimizing the binding poses obtained from docking [37], and refining the geometries of enzyme active sites obtained from a harmonically restrained minimization with MM [38], or X-ray structures [39]. It has been suggested that within the drug discovery process QM/MM is valuable for (1) helping the interpretation of poorly resolved electron density [39], (2) probing the details of the interactions within enzymes active sites, [40] and (3) investigating the effects of different substituents on the binding mode or in the assessment of alternate scaffolds [41].…”
Section: Qm/mmmentioning
confidence: 99%